Azide derivatized anticancer agents of vitamin K-3: X-ray structural, DSC, resonance spectral and API studies - Badave, Kirti D.; Patil, Yogesh; Gonnade, Rajesh G.; Srinivas, Darbha; Dasgupta, Rajan; Khan, Ayesha A.; Rane, Sandhya (Journal of Molecular Structure, 2011)
Compound 1 [1-imino (acetyl hydrazino)-Vitamin K-3], displays valence tautomerically related electronic isomers as Form land Form II. Form I exhibits 2D packing fragment with 1D ribbon chains of N-H center dot center dot center dot O hydrogen bonds and shows EPR silent features. While Form II is EPR active and exhibits biradical nature with double quantum transitions at g = 2.0040. H-1 NMR of compound 2, [1-imino (hydrazino carboxylate)-Vitamin K-3] and Form II exhibit pi delocalization via resonance assisted H-bonding [RAHB] effect compared to Form I. Molecular interactions in Form I and II are visualized by DSC. The electronic structures of compounds 1 and 2 have been correlated to their API values by measuring anticancer activities, mitochondrial potentials and DNA shearing patterns. Form II and compound 2 indicate mitochondria mediated apoptosis (similar to 75% cell death) while Form I causes 35% cell death. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Anticancer agents; API (Active Pharmaceutical Ingredients); Electronic isomers; RAHB (resonance assisted H-bonding); Vitamin K-3

Cu(II) conjugation along the transformation of a vitamin K-3 derivative to a dinaphthoquinone methide radical - Badave, Kirti D.; Patil, Shalaka S.; Khan, Ayesha A.; Srinivas, Darbha; Butcher, Raymond J.; Gonnade, Rajesh G.; Puranik, Vedavati G.; Pinjari, Rahul V.; Gejji, Shridhar P.; Rane, Sandhya Y. (New Journal of Chemistry, 2014)
1,1'-Methide-bi-vitamin K-3 (B) has been isolated as a dinaphthoquinone methide radical (DNQM) by the transformation of 1-imino(acetylhydrazino)-vitamin K-3 (A). The transformation follows a biomimetic activation pathway mediated via Cu(II) ion catalyzed oxidative coupling. Single crystal X-ray and electron spin resonance (ESR) experiments combined with density functional calculations elucidate the ``resonance structure'' of the DNQM radical (B). Fluorescence investigations reveal that DNQM facilitates interaction with the cysteine residue. As compared to the parent substrate, B shows a depletion in the level of GSH, triggering apoptosis in HeLa cells.